Improving students' financial literacy by training teachers using an online professional development module. Issue 1 (2nd January 2023) - Compen, Boukje; De Witte, Kristof; Declercq, Koen; Schelfhout, Wouter
ABSTRACT: We evaluate whether a scalable online teacher professional development (OTPD) module that requires little time investment enhances students' financial literacy. Two randomised controlled trials were performed, with 1827 students, 53 teachers and 47 schools participating. The financial education programme on its own increased students' financial knowledge, but did not improve financial behaviour. Regarding the OTPD effects, we observed that students' knowledge scores did not significantly improve, but that behaviour scores were enhanced relative to students whose teachers did not receive access to the OTPD module. In comparison with students in the control condition, behaviour scores improved with 0.39 SD.